2015
DOI: 10.1007/s13592-015-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, pathogens, and pests of honeybees in Asia

Abstract: Asia is home to at least nine honeybee species, including the introduced Apis mellifera. In addition to A. mellifera and Apis cerana being widely employed for commercial beekeeping, the remaining nonmanaged species also have important ecological and economic roles on the continent. Species distributions of most honeybee species overlap in Southeast Asia. This promotes the potential for interspecific transmission of pests and parasites and their spread to other parts of the world by human translocation. The dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 163 publications
0
62
0
1
Order By: Relevance
“…Honey bees are the most economically valuable pollinators in the world (Gallai et al ., ). Nevertheless, honey bees are attacked by numerous parasites and pathogens, such as ectoparasitic mites, microsporidia, fungi, viruses, and bacteria (Chen et al ., , ; Evans & Schwarz, ; McMenamin & Genersch, ; Chantawannakul et al ., ; Tehel et al ., ). One of the most destructive diseases affecting honey bee larvae is American foulbrood (AFB) disease caused by a Gram‐positive, spore‐forming bacterial pathogen, Paenibacillus larvae (Ebeling et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Honey bees are the most economically valuable pollinators in the world (Gallai et al ., ). Nevertheless, honey bees are attacked by numerous parasites and pathogens, such as ectoparasitic mites, microsporidia, fungi, viruses, and bacteria (Chen et al ., , ; Evans & Schwarz, ; McMenamin & Genersch, ; Chantawannakul et al ., ; Tehel et al ., ). One of the most destructive diseases affecting honey bee larvae is American foulbrood (AFB) disease caused by a Gram‐positive, spore‐forming bacterial pathogen, Paenibacillus larvae (Ebeling et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, honey bees are attacked by numerous parasites and pathogens, such as ectoparasitic mites, microsporidia, fungi, viruses, and bacteria (Chen et al, 2004Evans & Schwarz, Correspondence: Panuwan Chantawannakul, Bee Protection Laboratory, Department of Biology, Faculty of Science, Chiang Mai University, Chiang Mai 50200, Thailand. Tel: +66 05 3943346; fax: +66 053892259; email: panuwan@gmail.com 2011;McMenamin & Genersch, 2015;Chantawannakul et al, 2016;Tehel et al, 2016). One of the most destructive diseases affecting honey bee larvae is American foulbrood (AFB) disease caused by a Gram-positive, spore-forming bacterial pathogen, Paenibacillus larvae (Ebeling et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the commercial use and international trade of bees and bee products likely promotes the dispersal of diseases and pests [13,19,20,21]. Consequently, honeybees worldwide suffer from various pests and pathogens [21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Intensive production results in a higher probability of spreading diseases for the raising animals [46]. The experience from rearing bees has shown that animal-specific diseases might have negative economic outcomes [47]; thus, if the insects' production takes off for higher levels of intensive production, it is predictable that specific diseases might spread in the farms, and administration of veterinary drugs has to be considered, creating a problem with drug residues similar to that we face actually with meat from conventional husbandry [48,49]. Recording of all procedures and measures that have impact on food safety should be made continuously.…”
Section: Pre-requisites: Good Farming Practices and Good Practices Fomentioning
confidence: 99%